2007
DOI: 10.3233/jad-2007-11106
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Peripheral Endothelial Microvascular Responsiveness in Alzheimer's Disease

Abstract: Background: The concept that the neurotoxicity of amyloid β protein could partly result from vascular effects that may be detected in peripheral microcirculation is new. Methods: We compared peripheral endothelial vascular responses of patients with early clinically confirmed Alzheimer's disease (AD) to that of people with normal cognition and those with other forms of dementia. Acetylcholine (ACh) was iontophoresed into the skin and the resultant vasodilator response was measured using laser Doppler flowmeter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…Impaired of cerebral hemodynamics has been recently described in AD patients (Stefani et al 2009). Moreover, impaired peripheral endothelial responsiveness a assessed by laser Doppler flowmetery after acetylcholine activation in AD was found (Khalil et al 2007). Finally, microvascular damage and platelet abnormalities in early AD has been described (Borroni et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Impaired of cerebral hemodynamics has been recently described in AD patients (Stefani et al 2009). Moreover, impaired peripheral endothelial responsiveness a assessed by laser Doppler flowmetery after acetylcholine activation in AD was found (Khalil et al 2007). Finally, microvascular damage and platelet abnormalities in early AD has been described (Borroni et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…More interesting, Deane et al [34] have shown that, at the level of blood brain barrier, sVCAM-1 expression is increased by an up-regulation of RAGE (receptor for advanced end glycation products) caused by an increased flow of circulating free β amyloid [34]. Finally, an impairment in peripheral endothelial micro vascular responsiveness has been recently reported in Alzheimer's patients [35].…”
Section: Soluble Vascular Cell Adhesion Molecule 1 (Svcam-1)mentioning
confidence: 96%
“…31 Another study showed that in patients with AD or MCI, discernible changes were detected in endothelial function, compared with controls of similar age. 32 Both these studies imply that vascular and endothelial dysfunction may be the primary event, before the onset of the clinical syndrome of AD.…”
Section: Potential Mechanisms By Which Cerebrovascular Burden Influenmentioning
confidence: 98%